Performance of Different Categories of Operators in Simulated Diagnostic Colonoscopy. (May 2015) - Fasoli, Renato; Pertile, Riccardo; Seligman, Sonia; de Pretis, Giovanni
<x xml:space="preserve">Abstract</x> The possible involvement, although limited to the diagnostic phase of the procedure, of nonmedical staff (particularly endoscopy nurses) in lower digestive endoscopy has recently been suggested. Computer-based simulators have demonstrated objective evaluation of technical skills in digestive endoscopy. The aim of this study was to evaluate basic colonoscopy skills of endoscopy nurses (naive operators), as compared with junior physician staff and senior endoscopists, through a virtual reality colonoscopy simulator. In this single-center, prospective, nonrandomized study, 3 groups of digestive endoscopy operators (endoscopy nurses, junior doctors [<150 previous colonoscopies], expert doctors [>500 previous colonoscopies and >200/year]) completed six diagnostic cases generated by an endoscopic simulator (AccuTouch, Immersion Medical, Gaithersburg, MD). The performance parameters, collected by the simulator, were compared between groups. Five parameters have been considered for statistical analysis: time spent to reach the cecum; pain of any degree; severe/extreme pain; amount of insufflated air; percentage of visualized mucosa. Statistical analysis to compare the three groups has been performed by means of Wilcoxon test for two independent samples and by means of Kruskal–Wallis test for three independent samples (p < .05). Sixteen operators have been studied (six endoscopy nurses, five junior doctors, and five senior doctors); 96 colonoscopic procedures have been evaluated. Statistically significant differences between experts and naive operators were observed regarding time to reach the cecum and induction of severe/extreme pain, with both Kruskal–Wallis and Wilcoxon test (p < .05); all other comparisons did not reach statistical significance. Although, as expected, expert doctors exceeded both junior doctors and naive operators in some relevant quality parameters of simulated diagnostic colonoscopies, the results obtained by less expert performers—and particularly by nursing staff—appear satisfactory as in regards to most of the considered quality parameters and suggest a potential value of this device in effectively teaching basic lower digestive endoscopy to beginners in a relatively short time.